PENGEMBANGAN LKPD BERBASIS COMPUTATIONAL THINKING PADA BANGUN DATAR SEKOLAH DASAR - Pratiwi, Meliya Nur; Eka Sastrawati; Andi Gusmaulia Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a computational thinking–based student worksheet (LKPD) for elementary school plane geometry and to examine its validity, practicality, and effectiveness in improving fifth-grade students’ mathematical problem-solving skills. The research employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants included fifth-grade students, classroom teachers, and expert validators in mathematics content and instructional design. Research instruments comprised expert validation sheets, teacher and student response questionnaires, and mathematical problem-solving tests. Data were analyzed using percentage techniques to determine validity and practicality, as well as N-gain calculations to measure product effectiveness. The results indicated that the computational thinking–based worksheet met the criteria of valid, practical, and effective. The use of the worksheet significantly enhanced students’ mathematical problem-solving abilities in plane geometry. Therefore, the developed worksheet has the potential to serve as an innovative instructional material for elementary mathematics learning. Keywords: Student Worksheet, Computational Thinking, Plane Geometry, Elementary School, Mathematical Problem Solving.